Lip prints: The barcode of skeletal malocclusion - Pradeep Raghav; Naveen Kumar; Shishir Shingh; N Ahuja; Priyanka Ghalaut (Journal of Forensic Dental Sciences, 2013)
Introduction: In orthodontics, apart from essential diagnostic aids, there are so many soft tissue analyses in which lips are major part of concern. However, lip prints have never been used in orthodontics as diagnostic aid or forensic tool. Therefore, this study was designed to explore the possible association of lip prints with skeletal malocclusion. Materials and Methods: A sample of 114 subjects in the age group of 18-30 years, from North Indian adult population were selected on the basis of skeletal class I, class II and class III malocclusion, each comprising of 38 subjects with equal number of males and females. Lip prints of all the individuals were recorded and digital soft copies of lateral cephalograms were taken. Lip prints were compared between different skeletal malocclusions. Results: It was found that branched lip pattern was most common in North Indian adult population with no sexual dimorphism. The Z-test for proportion showed that the prevalence of vertical lip pattern was significantly higher in subjects having skeletal class III malocclusion. Conclusion: A definite co-relation of vertical lip patterns with skeletal class III malocclusion was revealed.